The Potential Role of Ferroptosis in Systemic Lupus Erythematosus - Chen, Qian; Wang, Jie; Xiang, Mengmeng; Wang, Yilun; Zhang, Zhixiong; Liang, Jun; Xu, Jinhua (Frontiers in Immunology, 2022)
Systemic lupus erythematosus (SLE) is an autoimmune disease that is accompanied with autoantibody production and inflammation. Other features of SLE pathogenesis include iron accumulation, oxidative stress, and lipid peroxidation, which are also major biochemical characteristics of ferroptosis, a novel non-apoptotic regulated form of cell death. To date, ferroptosis has been demonstrated to be an important driver of lupus progression, and several ferroptosis inhibitors have therapeutic effect in lupus-prone mice. Given the emerging link between ferroptosis and SLE, it can be postulated that ferroptosis is an integral component in the vicious cycle of immune dysfunction, inflammation, and tissue damage in SLE pathogenesis. In this review, we summarize the potential links between ferroptosis and SLE, with the aim of elucidating the underlying pathogenic mechanism of ferroptosis in lupus, and providing a new promising therapeutic strategy for SLE.